Thermodynamic, economic and environmental analyses of novel concentrated solar-PV-thermal integrated combined power, cooling and desalination system - Yadav V.K.; Sarkar J.; Ghosh P. (My University, 2025)
Solar concentrated photovoltaic-thermal collector integrated poly-generation system for simultaneous power, cooling and fresh water supply is highly promising for developing smart island/village. Hence, a novel system consisting of a concentrated photovoltaic-thermal collector, integrated organic Rankine cycle (for power), ejector refrigeration cycle (for cooling) and active solar still (for fresh water) is proposed. The system is analyzed based on energy, exergy, economic and environmental perspectives using three eco-friendly refrigerants, R152a, R1234ze[Z] and R1233zd[E], under various operating conditions. Seasonal performance and component sensitivity are evaluated as well. The novel system has the maximum value of the performance index of 0.351 as well as an overall exergy efficiency of 4.15 %, whereas annual total cost, as well as equivalent CO2 emission, are at their lowest values of 6125 $/yr and 301.7 tonnes/yr, respectively for R152a. Higher generator, as well as evaporator, temperature but a lower ambient (surrounding) temperature will be better for thermodynamic performance, but the annual cost, along with the equivalent CO2 emission, will increase. Performance index, along with the overall exergy efficiency, are highest in January and lowest in April, whereas annual cost, as well as CO2 emission, are lowest in June and highest in March. R152a is suggested as the best refrigerant for this proposed multi-generation system based on its performance as well as its eco-friendly nature. © 2023 Elsevier B.V.